Effective or Not? Building Discussions on Dilemmas and Refusals Into Research Practices: Perspectives From Participants - Toomey, Nisha (Journal of the Canadian Association for Curriculum Studies, 2020)
Within the academy, pedagogical practice includes how we teach about, design and conduct research. Too often, research has been carried out, in extractive ways, “on” Black, Indigenous, racialized and marginalized communities, rather than alongside them. Much of the research conducted in these communities centers on damage (Tuck, 2009) and operates on a faulty theory of change that imagines policymakers will adjust their systems just because scholars report on damage (Tuck & Yang, 2014). Using results from my dissertation field research, which built questions about the research process itself into my 32 qualitative interviews, this paper presents the perspectives of community members living and working along the Thailand-Myanmar border. It spotlights the usefulness of research and its potential to make change. I propose that to approach research in a more ethical and transformative way, academic researchers must include questions about the research itself into their fieldwork. Also, researchers should approach the work with healthy skepticism about why they are doing it at all, whether it’s already been done, and whether it could be done better by someone else. Participants offered concrete steps for how to make research more useful, involving as many community members/organizations as possible from the outset. They discussed only doing research based on long-term trusting relationships formed with communities; understanding cultural context; making consent forms easy to read, culturally appropriate and clear; sharing and collaborating on results with communities; making sure that publications and writing would be accessible; and using the research as a tool for advocacy or political activism outside the academy.